A cooperaperação policial e a partilha de informações, como fatores fundamentais na prevenção e no combate ao terrorismo extremista islâmico - Rato, Alexandra Maria Chambel (2022)
Jihadist terrorism, or violent extremist terrorism of Islamic origin, has become one of the main threats to the western way of life. In recent years, some of the countries of the European Union have been the target of several jihadist terrorist attacks by Islamic State affiliates. Following some of these terrorist attacks, serious failures in police cooperation and information sharing, have been found, that may have contributed so that it was not possible to prevent them or even avoid them. Thus, the European Union, recognizing the importance of information sharing in the prevention of terrorist attacks, has been building over time information systems and structures that have reinforced counterterrorism in Europe. As this is a matter that must, above all, be prevented, good police cooperation and good information sharing at a national, regional and international level is crucial for such prevention to be successful. In this regard, we aim to demonstrate with this study to what extent EU information systems, EU Agencies and informal information sharing forums have contributed, and continue to contribute, to effective police cooperation and rapid information sharing in order to prevent and combat jihadist terrorism. We also intend to point out what are the main limiting obstacles to full police cooperation and full information sharing between the security forces and services at European and national level. Thus, the work is structured in three main chapters: the first, theoretical and conceptual in nature, focuses on the conceptualization of the terrorism phenomenon, as well as the European and national legal framework for the prevention and combat of jihadist terrorism and the sharing of information; the second chapter sets out the importance of preventive investigation of this type of terrorism and the importance of information and intelligence systems in its prevention; the third chapter deals with the central theme of police cooperation and information sharing at European and national level, having sought to understand the main limiting obstacles to full police cooperation and full information sharing between the Forces and Security Services at European and national level.